MENINGKATKAN KREATIVITAS SISWA MEMAHAMI KONSEP SIFAT CAHAYA MELALUI PEMBELAJARAN KONTEKSTUAL DI SD - Muslimin, Muslimin; Irfan, Muhammad; Sahabuddin, Erma Suryani (Universitas Negeri Makassar, 2015)
This study aims to: (1) to plan contextual learning; (2) to carry out learning by using a contextual approach, (3) to understand the material properties of light after studying using a contextual approach. The study population is graders V Elementary School 240 Pinrang numbered 20 people. Data collection techniques of this study is to test, interviews, observation and field notes. The data analysis using descriptive statistical techniques to describe student learning outcomes. Results of the study are as follows; (1) using a contextual approach to the fifth grade students of Elementary School 240 Pinrang can improve kreativtas students in science subjects to the material properties of light, (2) the teacher is not maximized in designing lesson plans to use the approach of contextual, (3) an increase in students' creativity by using a contextual approach for students during the students learn more actively in the implementation of the learning process.